Case report: Single-cell mapping of peripheral blood mononuclear cells from a patient with both Crohn’s disease and isolated congenital asplenia - Pu, Dan; Liu, Lu; Wang, Na; Wang, Dandan; Zhang, Zhe; Feng, Baisui (Frontiers in Immunology, 2022)
Crohn's disease (CD), as one of the principal form of inflammatory bowel disease (IBD), is characterized by the chronic and recurring inflammatory conditions in the intestine resulting from the over-activation of intestinal immunity. Hyposplenism is strongly associated with CD, while the effect of human spleen on the differentiation and development of immune cell subsets in CD patients remains unclear. Isolated congenital asplenia (ICA) is an extremely rare condition characterised by the absence of a spleen at birth without any other developmental defects. Here, we describe the first case of a patient with both ICA and CD, and follow the progression of CD from remission to active stage. Using cytometry by time of flight (CyTOF) analysis, we draw the first single-cell mapping of peripheral blood mononuclear cells (PBMC) from this unique patient, tracing back to the innate or adaptive immune cell subsets and cell surface markers affected by the spleen. Based on our analysis, it is speculated that the spleen contributes to maintaining immune homeostasis, alleviating intestinal inflammation and improving prognosis by influencing the differentiation and development of peripheral immune cell subsets and the expression of cell surface markers in patients with CD.